Environmental enrichment for laboratory rats and mice: endocrine, physiological, and behavioral benefits of meeting rodents' biological needs - Domínguez-Oliva, Adriana; Hernández-Avalos, Ismael; Bueno-Nava, Antonio; Chávez, Cuauhtémoc; Verduzco-Mendoza, Antonio; Olmos-Hernández, Adriana; Villanueva-García, Dina; Avila-Luna, Alberto; Mora-Medina, Patricia; Martínez-Burnes, Julio; Gálvez-Rosas, Arturo; Mota-Rojas, Daniel (Frontiers in Veterinary Science, 2025)
Standard housing for laboratory rodents is characterized by cages that do not always provide an adequate environment to meet the animal's behavioral needs. When animals are reared under impoverished conditions, negative states such as boredom and distress might arise. Environmental enrichment (EE) is an alternative to expose rodents to physical, sensory, cognitive, and/or social stimulation greater than the one received under standard housing conditions. The present review aims to discuss the main physiological, endocrine, and behavioral effects of environmental enrichment in murine research models. The positive and negative effects will be addressed, as well as factors including enrichment-related (i.e., type of EE, duration of EE) and animal-related aspects (i.e., strain, sex, or age) that need to be considered by researchers when adopting EE for laboratory rodents. It was observed that EE decreases corticosterone concentrations in rodents, an indication of lower levels of stress. Likewise, tachycardia, hypertension, and shorter heart rate variability are ameliorated with the implementation of EE (reflecting a beneficial effect). Among the behavioral benefits, rodents reared under EE have anti-anxiety characteristics, increased exploratory behavior, and less fear-related responses than standard-housed animals. However, in some cases, increased aggression has been reported. Although there is no standardization for EE, to properly adopt EE in experimental facilities, researchers must consider enrichment- and animal-related factors to improve the welfare of laboratory rodents.